2015
DOI: 10.1002/anie.201411329
|View full text |Cite
|
Sign up to set email alerts
|

CuSbS2‐Sensitized Inorganic–Organic Heterojunction Solar Cells Fabricated Using a Metal–Thiourea Complex Solution

Abstract: The device performance of sensitizer-architecture solar cells based on a CuSbS2 light sensitizer is presented. The device consists of F-doped SnO2 substrate/TiO2 blocking layer/mesoporous TiO2 /CuSbS2 /hole-transporting material/Au electrode. The CuSbS2 was deposited by repeated cycles of spin coating of a Cu-Sb-thiourea complex solution and thermal decomposition, followed by annealing in Ar at 500 °C. Poly(2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b']dithiophene)-alt-4,7(2,1,3-benzothiadiazole)) (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…Semiconducting metal chalcogenides include a broad range of photovoltaic materials, such as the conventional Cu(In, Ga)Se 2 (CIGS), CdTe and Cu 2 ZnSn(S, Se) 4 . Recently, Zn−Cu−In−Se alloy, AgBiS 2 , CuSbS(Se) 2 , PbS, Sb 2 S 3 , Sb 2 Se 3 have attracted intensive attention as low‐cost and stable light absorbing materials; their initial applications in solar cells have generated decent power conversion efficiencies (PCE). Among them, Sb 2 S 3 and Sb 2 Se 3 are binary compounds with relatively environment‐friendly elements.…”
Section: Methodsmentioning
confidence: 99%
“…Semiconducting metal chalcogenides include a broad range of photovoltaic materials, such as the conventional Cu(In, Ga)Se 2 (CIGS), CdTe and Cu 2 ZnSn(S, Se) 4 . Recently, Zn−Cu−In−Se alloy, AgBiS 2 , CuSbS(Se) 2 , PbS, Sb 2 S 3 , Sb 2 Se 3 have attracted intensive attention as low‐cost and stable light absorbing materials; their initial applications in solar cells have generated decent power conversion efficiencies (PCE). Among them, Sb 2 S 3 and Sb 2 Se 3 are binary compounds with relatively environment‐friendly elements.…”
Section: Methodsmentioning
confidence: 99%
“…[ 1 ] The performance of cells using the perovskite materials [2][3][4][5][6][7][8] has already surpassed that of both conventional dye-sensitized and organic photovoltaics as well as inorganic nanoparticle (including quantum dots)-based solar cells. [9][10][11][12][13][14] This mainly stems from the easy band gap tuning by managing the chemical composition, [ 5,7 ] large optical absorption, high carrier mobility, and very long electron-hole diffusion lengths. [ 15,16 ] The materials for perovskite solar cells (PSCs) have been prepared by the dissolution of stoichiometric MAI or FAI and PbI 2 , etc.…”
Section: Doi: 101002/aenm201502104mentioning
confidence: 99%
“…Moreover, Tang and co‐workers reported that CuSbS 2 had superior defect physics with extremely low concentration of recombination‐center defects . Meanwhile, CuSbS 2 thin film solar cell had also been fabricated . These works indicate that CAS may represent a promising new material for photovoltaic applications.…”
Section: Introductionmentioning
confidence: 99%